Effect of Emulsion pH and Humectants on Sensory and Physico-Chemical Quality of Hurdle Treated Chicken Sausages - Karle, S.D.; Rindhe, S.N.; Suryawanshi, S.U.; Devangare, A.A.; Verma, S.K. (Journal of Meat Science, 2015)
The aim of this study was to develop acceptable quality of shelf stable chicken sausages using hurdle technology. Hurdles incorporated were humectants textured soya protein and low emulsion pH. Different parameters evaluated were pH, emulsion stability, cooking yield, moisture, protein, fat and sensory attributes. Incorporation of TSP at 4% level significantly (p
Keywords: Chicken sausages; Emulsion pH; Hurdle technology; Textured soya protein